-1
$\begingroup$

For real numbers $x, y$ satisfy the condition $x>0, y>0$ and $$\log _{\sqrt{3}}\left(\frac{x+y}{x^2+y^2+xy+2}\right)=x\left(x-3\right)+y\left(y-3\right)+xy$$ Find the largest value of the expression $$P=\frac{3x+2y+1}{x+y+6}$$

$\endgroup$

closed as off-topic by Aqua, qbert, eranreches, Nosrati, José Carlos Santos Dec 27 '17 at 18:28

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Aqua, qbert, eranreches, Nosrati, José Carlos Santos
If this question can be reworded to fit the rules in the help center, please edit the question.

  • 1
    $\begingroup$ there are a couple things wrong with the way this was asked in my opinion: 1) you put none of your thoughts and just copy pasted a problem you are working on 2) your tags make it unclear if you would accept a solution using calculus, as the one below does (and would certainly be the way I would expect it to be solved) $\endgroup$ – qbert Dec 27 '17 at 9:24
  • $\begingroup$ @Mary: You said you know a little english. Are you from Shanghai, China? $\endgroup$ – DeepSea Dec 27 '17 at 13:17
  • $\begingroup$ I am from Vietnam. $\endgroup$ – Mary Jan 3 '18 at 2:47
2
$\begingroup$

I think this is a very nice question.

We have $$P(x,y)=\frac{3x+2y+1}{x+y+6}\tag{1}$$ so by the Quotient Rule $$P'(x,y)=\frac{(3+2y')(x+y+6)-(3x+2y+1)(1+y')}{(x+y+6)^2}=\frac{y+(11-x)y'+17}{(x+y+6)^2}=0$$ for stationary points. Thus $$(11-x)y'+y+17=0\implies y'+\frac1{11-x}y=-\frac{17}{11-x}$$ is a first-order linear ODE, which is easy to solve.

Here $p(x)=\dfrac1{11-x}$ and $q(x)=-\dfrac{17}{11-x}$. The integrating factor is $$h(x)=\exp\left(\int p(x)\, dx\right)=\frac1{11-x}$$ so we solve $$y\cdot p(x)=\int p(x)q(x)\, dx \implies \frac y{11-x}=\int -\frac{17}{(11-x)^2}\, dx=-\frac{17}{11-x}+c$$ where $c$ is a constant. Hence $$y=-17-c(x-11)=-17+11c-cx\tag{2}$$ Plugging this back into $(1)$, we get $$\max P=\frac{3x-34+22c-2cx+1}{x-17+11c-cx+6}=\frac{(3-2c)(x-11)}{(1-c)(x-11)}=\frac{3-2c}{1-c}\tag{3}$$ Now let $x=0$. Then by $(2)$, we have $$y(0)=-17+11c\implies c=\frac1{11}(y(0)+17)\tag{4}$$ We are given the condition that $$\log _{\sqrt{3}}\left(\frac{x+y}{x^2+y^2+xy+2}\right)=x\left(x-3\right)+y\left(y-3\right)+xy$$ so $$\log_{\sqrt3}\left(\frac y{y^2+2}\right)=y(y-3)$$ This has solutions when $y=1, 2$.

Therefore, when $y=1$, $c=\dfrac{18}{11}$ from $(4)$ and so from $(3)$,$$P_{y=1}=\frac{3-2\left(\frac{18}{11}\right)}{1-\frac{18}{11}}=\frac37$$ and when $y=2$, $c=\dfrac{19}{11}$ from $(4)$ and so from $(3)$, $$P_{y=2}=\frac{3-2\left(\frac{19}{11}\right)}{1-\frac{19}{11}}=\frac58$$ Since $\dfrac58>\dfrac37$, $$\boxed{\max P = \frac58.}$$

$\endgroup$
  • $\begingroup$ why do you assume $y$ is a function of $x$ here? $\endgroup$ – qbert Dec 27 '17 at 9:26
  • $\begingroup$ @qbert I am not aware of any other method to solve this (since the condition has $\log$ on LHS and polynomials on the right - using the Lambert W function would be very complicated) Also, $y$ boils down to have a linear relationship with $x$. Is my answer wrong? $\endgroup$ – TheSimpliFire Dec 27 '17 at 9:31
  • $\begingroup$ I'm not sure, you could probably justify this with the implicit function theorem on the constraint condition. I am certainly not claiming it is wrong, I was just wondering if you had a justification $\endgroup$ – qbert Dec 27 '17 at 9:32
-1
$\begingroup$

Unfortunately I'm in high school so I do not understand your solution at "a first-order linear ODE". According to my ability, from the condition of the problem I just exploited: ${{\log }_{\sqrt{3}}}\left( \frac{x+y}{{{x}^{2}}+{{y}^{2}}+xy+2} \right)=x\left( x-3 \right)+y\left( y-3 \right)+xy$ $\Leftrightarrow 2{{\log }_{3}}\left( x+y \right)-2{{\log }_{3}}\left( {{x}^{2}}+{{y}^{2}}+xy+2 \right)={{x}^{2}}+{{y}^{2}}+xy-3\left( x+y \right)$ $\Leftrightarrow 2{{\log }_{3}}3\left( x+y \right)+3\left( x+y \right)=\left( {{x}^{2}}+{{y}^{2}}+xy+2 \right)+2{{\log }_{3}}\left( {{x}^{2}}+{{y}^{2}}+xy+2 \right)$ $\Leftrightarrow 3\left( x+y \right)={{x}^{2}}+{{y}^{2}}+xy+2$

Please help me complete the problem solving on high school mathematics knowledge. (Sympathy for me because I know a little English so I have to use "Google translate" translation)

$\endgroup$

Not the answer you're looking for? Browse other questions tagged or ask your own question.